Effect of irradiance on growth, physiological processes and yield of melon (Cucumis mela) plants grown in hydroponics - Ismail, Mohd Razi; Yusoff, Mohd Kamil (Universiti Putra Malaysia Press, 1996)
The effect of different irradiance levels on melon (Cucumis mela) cv. Birdie, Charity Ball and Jade Dew grown in hydroponics was investigated. Plants were exposed to mean daily irradiance levels of 11.4,8.2, 6.1 and 3.0 MJ m-2 day-1 achieved by using different levels of shade. The dry matteryield appeared to be directly proportional to the irradiance level received by plants. Stomatal conductance and photosynthetic rate were highest when the plants were grown under the highest irradiance level. Plants grown under 11.4 MJ m-2aI had the highest fruit fresh weight and total soluble solids. All cultivars failed to fruit when grown under irradiance of 3.0 MJ m-2aI .